2021
DOI: 10.3390/catal11030395
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxygenation of Heterostilbenes—Batch versus Microflow Reactor

Abstract: On the basis of earlier results with furan and thiophene derivatives of benzobicyclo[3.2.1]octadiene, photocatalytic oxygenation of novel furo- and thieno heterostilbenes with water-soluble manganese(III) porphyrins offered suitable possibilities to study their reactivities and reaction pathways depending on the heteroatom and the catalyst charge. The experiments were carried out in two reactors types (batch and microflow) to investigate the geometric effects. NMR spectroscopy, GC, and UPLC/MS analyses were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Horváth, Škoric, and co-workers reported the photocatalytic oxidation of heterostilbenes . Manganese­(III) porphyrins worked as the photocatalyst.…”
Section: Flow Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Horváth, Škoric, and co-workers reported the photocatalytic oxidation of heterostilbenes . Manganese­(III) porphyrins worked as the photocatalyst.…”
Section: Flow Photochemistrymentioning
confidence: 99%
“…Horvath, S ̌koric, and co-workers reported the photocatalytic oxidation of heterostilbenes. 756 Manganese(III) porphyrins worked as the photocatalyst. Differently from metal-free porphyrins, these catalysts perform an electron transfer after light irradiation, affording Mn(IV) and Mn(V) complexes which are then involved in follow-up reactions.…”
Section: Photodecarboxylations and -Carboxylationsmentioning
confidence: 99%
“…These catalysts can be easily separated from the target products but their reuse was impossible probably due to their low photostability. [119][120][121] To knowledge, we report here the first example of an oxidation reaction in which water-soluble porphyrins can be recycled and reused.…”
Section: Dalton Transactions Papermentioning
confidence: 96%
“…It is noteworthy that the photocatalytic properties of watersoluble Mn(III) complexes for oxygenation of unsaturated compounds were thoroughly investigated. [119][120][121] In the case of sulfonate-substituted porphyrin derivatives, it was shown that free-base porphyrins can also be used as PCs. These catalysts can be easily separated from the target products but their reuse was impossible probably due to their low photostability.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Water-soluble metalloporphyrins, due their special spectral, coordination, and photoredox features, offer numerous possibilities of application in various photochemical procedures, e.g., for visible light-driven photocatalysis [ 1 , 2 , 3 , 4 , 5 , 6 ]. These peculiar coordination and electronic properties are due in large part to the structure of the porphyrin ligand.…”
Section: Introductionmentioning
confidence: 99%